2013
DOI: 10.1371/journal.pone.0054036
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methyltransferase Inhibitor Zebularine Inhibits Human Hepatic Carcinoma Cells Proliferation and Induces Apoptosis

Abstract: Hepatocellular carcinoma is one of the most common cancers worldwide. During tumorigenesis, tumor suppressor and cancer-related genes are commonly silenced by aberrant DNA methylation in their promoter regions. Zebularine (1-(β-D-ribofuranosyl)-1,2-dihydropyrimidin-2-one) acts as an inhibitor of DNA methylation and exhibits chemical stability and minimal cytotoxicity both in vitro and in vivo. In this study, we explore the effect and possible mechanism of action of zebularine on hepatocellular carcinoma cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
1
28
0
Order By: Relevance
“…In this study, we found that neither 5-aza-dC nor RG108 treatment could affect PKR phosphorylation or PKR protein level (Fig. 7A,B), while it is known that zebularine treatment downregulates PKR phosphorylation and PKR protein level in HepG2 cells22. These findings indicate that 5-aza-dC and RG108 affect DNMT1 activity but not PKR.…”
Section: Resultsmentioning
confidence: 50%
See 3 more Smart Citations
“…In this study, we found that neither 5-aza-dC nor RG108 treatment could affect PKR phosphorylation or PKR protein level (Fig. 7A,B), while it is known that zebularine treatment downregulates PKR phosphorylation and PKR protein level in HepG2 cells22. These findings indicate that 5-aza-dC and RG108 affect DNMT1 activity but not PKR.…”
Section: Resultsmentioning
confidence: 50%
“…In our previous study22, we reported that zebularine treatment downregulated the expression of DNMT1 protein in HepG2 cells, implying that zebularine can upregulate the expression levels of CYP genes through suppressing the expression of DNMT1. To examine the action mechanism by which zebularine upregulates the expression levels of CYP genes, we knocked down DNMT1 gene expression in HepG2 cells and examined the expression levels of CYP genes.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This calculated value, known as β, ranges from 0 (completely unmethylated) to 1 (fully methylated). Nakamura et al [17], Yuen et al [18], and Córdova-Palomera et al [19] proposed that a difference in methylation between 2 groups is significant if it is >10%. We adopted this assumption, setting a threshold at 10%, i.e., a difference in β between BR and WR (Δβ) >10% (|Δβ| >0.1) was defined as a significant difference.…”
Section: Methodsmentioning
confidence: 99%